Dust explosion: Raising awareness of combustible dust hazard - S. I., Rani; Jolius, Gimbun; B. A., Aziz (AIP, 2024)
Dust explosion is a serious global industrial hazard since it can lead to property damage and business interruption as well as injuries and fatalities. Statistics shows increasing number of dust explosion incidents in industries around the world and discovered frequency of occurrence in 21st century. Hence, proper knowledge of dust explosion fundamentals such as dust explosion factors and dust explosibility are very important in preventing and mitigating this industrial hazard. Legislations and safety codes should be strictly followed by the industries since the mushrooming growths of industrial sectors all over the world. Lessons learned from the past incidents warrant the critical need for further sequence analysis. Safety education is essential to enhance awareness in the workplace and community for sustainable development.